Weed Suppression and Performance of Grain Legumes Following an Irrigated Rice Crop in Southern Australia - K. M. Shamsul Haque; Brian Dunn; Geoff Beecher; Philip L. Eberbach; Mike Dyall-Smith; Julia A. Howitt; Leslie A. Weston (Agronomy, 2016)
Post-rice irrigated soils offer several potential advantages for the growth of subsequent crops, but Australian producers have often been reluctant to grow grain legumes immediately following a rice crop due to physico-chemical constraints. A field experiment was thus conducted to explore the potential for producing grain legumes following rice in comparison to those following a fallow during 2012 and 2013. Two grain legumes, field pea and faba bean, were sown 5, 7 and 12 weeks after rice harvest in 2013 at Yanco, NSW, and plant growth indicators and grain yield were compared. Early sowing of field pea following rice gave the best outcome, with plants flowering three weeks earlier and yielding 1330 kg·ha−1 more grain than after fallow. In contrast, faba bean yield was 35 kg·ha−1 less after rice than after fallow across the three sowing dates. Higher pea yield was consistent with the early emergence of seedlings, higher light interception and overall greater plant growth following rice. Post-rice crops also had 10-fold less weed infestation than crops in a similarly-established fallow treatment and, thus, required far less weed management. Legume crops sown at the later seeding date had significantly reduced (~50%–60%) yields compared to those of the first two sowings; this is most likely a reflection of reduced temperatures and day lengths experienced during vegetative and reproductive growth phases.